Synthesis of ternary geopolymers based on metakaolin, boiler slag and rice husk ash (2015)
Ternary mixtures of geopolymers obtained from the alkaline activation of metakaolin (MK), boiler slag (BS), and rice husk ash (RHA) using a solution of potassium hydroxide were mechanically, thermally, and microstructurally characterized. The geopolymer properties and final microstructures indicate that the addition of BS, despite containing large amounts of unburned material (16.36%), allows for greater densification and greater homogeneity of the geopolymeric gel, which results in greater stability in strength at long curing ages. Substitution of 30% of MK by BS results in an increase in compressive strength of up to 21% and 122% after 28 and 180 days of curing, respectively. These results demonstrate the possibility of the construction sector using geopolymers based on MK and adding BS and RHA to obtain cementitious materials with a lower environmental impact.